Gut-Brain Axis, Notch, and Brain Cancer: ‘The Rising Three’ - Gembong Satria Mahardhika; Norina Agatri (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights The gut-brain axis (GBA) is a bidirectional communication network linking the gastrointestinal tract and the central nervous system (CNS), involving neurons and various signaling molecules such as endocrine, humoral, metabolic, and immunological factors. The Notch signaling pathway is implicated in the development of brain tumors, including gliomas, which show elevated Notch receptor levels. This pathway is critical in tumor cell proliferation, survival, and invasiveness. Abstract Background: The gut-brain axis (GBA) facilitates reciprocal communication between the central and enteric nervous systems. The connection between the GBA, Notch, and brain cancer is a complex and intricate subject that warrants further exploration. Brain cancer has a multifaceted pathophysiology and structure, making the journey from diagnosis to treatment challenging. The involvement of Notch in the signaling pathway could be relevant to both brain cancer and the gut-brain axis. Objective: This research aimed to examine the complex interplay between the gut-brain axis (GBA), Notch signaling, and brain cancer, specifically gliomas. Material and Method: This study was a scoping review conducted using multiple search engines, including PubMed, ProQuest, and Cambridge Core, spanning from 2018 to 2023. The collected materials were filtered and subsequently analyzed. Result: The existence of the gut-brain axis is a fascinating topic for in-depth exploration. The complex relationship between Notch and the gut-brain axis may offer valuable insights into the pathogenesis of brain cancer. The literature review identified two publications, which were analyzed in more detail. The gut-brain axis (GBA) refers to a bidirectional communication network between the central nervous system and the enteric nervous system, regulating gastrointestinal functions. The identification of the Notch signaling pathway suggests its role in the development of brain tumors. Conclusion: The connections between the gut-brain axis, Notch, and brain cancer are evident. The Notch pathway, as a signaling mechanism, is linked to brain cancer, and the gut-brain axis is also associated with it. This interconnected relationship has the potential to uncover novel avenues for diagnosis and therapy, warranting further research.